Fusion of purple membranes triggered by immobilization on carbon nanomembranes - Riedel, René (Beilstein J Nanotechnol, 2021)
A freestanding ultrathin hybrid membrane was synthesized comprising two functional layers, that is, first, a carbon nanomembrane (CNM) produced by electron irradiation-induced cross-linking of a self-assembled monolayer (SAM) of 4′-nitro-1,1′-biphenyl-4-thiol (NBPT) and second, purple membrane (PM) containing genetically modified bacteriorhodopsin (BR) carrying a C-terminal His-tag. The NBPT-CNM was further modified to carry nitrilotriacetic acid (NTA) terminal groups for the interaction with the His-tagged PMs forming a quasi-monolayer of His-tagged PM on top of the CNM-NTA. The formation of the Ni-NTA/His-tag complex leads to the unidirectional orientation of PM on the CNM substrate. Electrophoretic sedimentation was employed to optimize the surface coverage and to close gaps between the PM patches. This procedure for the immobilization of oriented dense PM facilitates the spontaneous fusion of individual PM patches, forming larger membrane areas. This is, to our knowledge, the very first procedure described to induce the oriented fusion of PM on a solid support. The resulting hybrid membrane has a potential application as a light-driven two-dimensional proton-pumping membrane, for instance, for light-driven seawater desalination as envisioned soon after the discovery of PM.